PENYULUHAN PENGHITUNGAN BREAK EVEN POINT PADA USAHA KERUPUK KEMPLANG & PEMPEK Hj. EVA YUNUS PALEMBANG - Lisnini Lisnini; Elisa Elisa; Munfaridi Munfaridi; G Oka Windarti; M Yusuf (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The dedication to this community is entitled Counseling on Break Even Point (BEP) Analysis in the Kerupuk Kemplang and Pempek Hj Eva Yunus Business in Palembang City, located on Jl KH. A. Azhari Lorong Anten-anten no. 576 RT. 16 RW.04 Kelurahan 5 Ulu Palembang is under the auspices of PT Pusri Palembang. This business is a family business (home industry) and since 1990 this business has been held by Hj Eva Yunus. Previously this business belonged to Hj Eva Yunus's parents. Since 2012 development has been carried out with additional products namely; pempek, model or tekwan, previously only kerupuk and kemplang only. Based on problems related to the calculation of Break Even Point (BEP) in the Kerupuk Kemplang and Pempek Business Hj Eva Yunus in Palembang City, and how to calculate the Break Even Point (BEP) in the Kerupuk Kemplang and Pempek Business, and how many units that must be generated so that the company earns a profit which is expected. In this effort, the author sees that there are not 5 direct workers and 5 indirect workers. The initial capital of Rp. 500,000.00 (in 1990) after the development of this business was fostered by PT Pusri. They get a loan of IDR 50,000,000 - IDR 70,000,000 per 2 years with an interest of 3%. In this business, the business owner is not counted as labor and the building where the business is located is not counted, nor are his nephews or workers working in the house. So by giving a BEP Analysis counseling, it is expected that business owners can calculate the BEP in units and the BEP in rupiah can also determine the expected profit.